2020
DOI: 10.1002/jbm.a.36985
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment stimulus on erythrocyte compatibility and hemostatic behavior of one‐dimensional bioactive nanostructures

Abstract: This study identifies the role and significance of heat treatment parameters on blood compatibility and hemostatic performances. Bioactive nanomaterials step annealed at 550 and 600°C enhances the biocompatibility due to the liberation of nitrate content. This also develops the anisotropic structures such as needle‐like and rod‐like appearances that positively improve the erythrocyte compatibility. Different stable crystalline phases such as NaCaPO4, Na2Ca2Si3O9, and Na1.8Ca1.1Si6O14 were observed for all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Boccaccini et al reported that further increasing the sintering temperature between 800 and 950 °C yields a phosphate-rich silicorhenanite (Na 2 Ca 4 (PO 4 ) 2 SiO 4 ) phase . On the other hand, Shivalingam et al reported that higher sintering temperatures might reduce the bioactivity and biocompatibility of the prepared bioactive glass material . Thus, the biomaterial sintered at 800 °C yielded the Na 4 Ca 4 Si 6 O 18 phase reported to form an amorphous calcium phosphate layer on immersion in simulated body fluid and delayed crystallization to the hydroxyapatite phase.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Boccaccini et al reported that further increasing the sintering temperature between 800 and 950 °C yields a phosphate-rich silicorhenanite (Na 2 Ca 4 (PO 4 ) 2 SiO 4 ) phase . On the other hand, Shivalingam et al reported that higher sintering temperatures might reduce the bioactivity and biocompatibility of the prepared bioactive glass material . Thus, the biomaterial sintered at 800 °C yielded the Na 4 Ca 4 Si 6 O 18 phase reported to form an amorphous calcium phosphate layer on immersion in simulated body fluid and delayed crystallization to the hydroxyapatite phase.…”
Section: Resultsmentioning
confidence: 99%
“…25 On the other hand, Shivalingam et al reported that higher sintering temperatures might reduce the bioactivity and biocompatibility of the prepared bioactive glass material. 13 Thus, the biomaterial sintered at 800 °C yielded the Na 4 Ca 4 Si 6 O 18 phase reported to form an amorphous calcium phosphate layer on immersion in simulated body fluid and delayed crystallization to the hydroxyapatite phase. Another dominant phase observed in the E-Si-P biomaterial is the hexagonal structured Ca 5 (PO 4 ) 3 (OH) hydroxyapatite phase well matched with JCPDS #86-0740.…”
Section: Thermal Analysismentioning
confidence: 96%
See 3 more Smart Citations